2015
DOI: 10.1007/s00253-015-7171-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and heterologous expression of a Xanthophyllomyces dendrorhous α-glucosidase with potential for prebiotics production

Abstract: Basidiomycetous yeast Xanthophyllomyces dendrorhous expresses an α-glucosidase with strong transglycosylation activity producing prebiotic sugars such as panose and an unusual tetrasaccharides mixture including α-(1-6) bonds as major products, which makes it of biotechnological interest. Initial analysis pointed to a homodimeric protein of 60 kDa subunit as responsible for this activity. In this study, the gene Xd-AlphaGlu was characterized. The 4131-bp-long gene is interrupted by 13 short introns and encodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
(49 reference statements)
1
16
0
Order By: Relevance
“…By 24 h of reaction with 500 mM maltose, the amount of transglycosylation products was 12.6% of total sugars in the reaction mixture, while the respective value for the MAL62 protein was about three times less-4.5% (see Table S3). Many α-glucosidases can transglycosylate and produce short oligosaccharides, especially at high concentration of the substrate [17][18][19][20][21]. We assayed this possibility by incubating BaAG2 with 250 and 500 mM maltose up to 72 h and analyzed the reaction products by HPLC.…”
Section: The Transglycosylation Of Maltosementioning
confidence: 99%
See 2 more Smart Citations
“…By 24 h of reaction with 500 mM maltose, the amount of transglycosylation products was 12.6% of total sugars in the reaction mixture, while the respective value for the MAL62 protein was about three times less-4.5% (see Table S3). Many α-glucosidases can transglycosylate and produce short oligosaccharides, especially at high concentration of the substrate [17][18][19][20][21]. We assayed this possibility by incubating BaAG2 with 250 and 500 mM maltose up to 72 h and analyzed the reaction products by HPLC.…”
Section: The Transglycosylation Of Maltosementioning
confidence: 99%
“…Phaffia rhodozyma) has been studied in detail, and synthesis of tri-and tetrasaccharides with α-1,6 linkages was detected. This enzyme certainly has a biotechnological potential-it produced 3.6 times more transglycosylation products than the S. cerevisiae α-glucosidase studied at the same conditions [17,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was extensively reported that the hydrolytic activity of glycosidases, such as α/β‐glucosidases or β‐fructofuranosidases, could be shifted towards synthesis (trasnsglycosylating activity) using a high substrate concentration. Thus, the α‐glucosidase from the yeast Xanthophyllomyces dendrorhous produced IMOS (mainly panose) using 200–525 g l −1 maltose (Fernández‐Arrojo et al , ; Gutierrez‐Alonso et al , ) and β‐fructofuranosidases from Aspergillus awamori or yeast such as Schwanniomyces occidentalis and Saccharomyces cerevisiae synthesized FOS using different sucrose‐rich by‐products from a variety of palm tree dates (the first) or 600 g l −1 sucrose (the last two) (Álvaro‐Benito et al , ; Lafraya et al , ; Smaali et al , ). In fact, sucrose is a relatively cheap and renewable raw material that has already been widely employed in the synthesis of bioactive oligosaccharides (Monsan and Ouarné, ), and among them several hetero‐oligosaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the promoter for crtS contains four consensus motifs for the binding of CreA [13], which is a negative regulator involved in catabolic repression in Aspergillus nidulans [18]. In addition, extracellular α-glucosidase and invertase activities were not detected in X. dendrorhous cultures when glucose was used as a carbon source, suggesting the catabolic repression of these enzymes [19, 20]. This indicates that this regulatory mechanism is operative in X. dendrorhous , as genes encoding glycosyl hydrolases are well known as targets of catabolic repression.…”
Section: Introductionmentioning
confidence: 99%